Direct and cost-efficient hyperpolarization of long-lived nuclear spin states on universal 15N2-diazirine molecular tags - Theis, Thomas; Ortiz, Gerardo X.; Logan, Angus W. J.; Claytor, Kevin E.; Feng, Yesu; Huhn, William P.; Blum, Volker; Malcolmson, Steven J.; Chekmenev, Eduard Y.; Wang, Qiu; Warren, Warren S. (Science advances, 2016)
More than 10,000-fold enhanced magnetic resonance signals with >20-min signal lifetimes on universal biomolecular markers. Conventional magnetic resonance (MR) faces serious sensitivity limitations which can be overcome by hyperpolarization methods, but the most common method (dynamic nuclear polarization) is complex and expensive, and applications are limited by short spin lifetimes (typically seconds) of biologically relevant molecules. We use a recently developed method, SABRE-SHEATH, to directly hyperpolarize 15 N 2 magnetization and long-lived 15 N 2 singlet spin order, with signal decay time constants of 5.8 and 23 minutes, respectively. We find >10,000-fold enhancements generating detectable nuclear MR signals that last for over an hour. 15 N 2 -diazirines represent a class of particularly promising and versatile molecular tags, and can be incorporated into a wide range of biomolecules without significantly altering molecular function.